INFLUENCE OF ISLAMIC CORPORATE GOVERNANCE AND INTELLECTUAL CAPITAL ON BUSINESS SUSTAINABILITY THROUGH FINANCIAL PERFORMANCE AS MEDIATION VARIABLES IN SHARIA BANKING FOR THE 2016 – 2020 PERIOD - Cholis Hidayati; Gustaf Naufan Febrianto (SEAN Institute, 2022)
Islamic banking is an alternative banking service for Muslim customers who want to choose non-usury and minimal risk banking services. However, the comparison of market share, total core capital owned by Islamic banking with conventional banking is one of the challenges for Islamic banking to maintain its business continuity the period of 2016 – 2020. The design of this study uses a descriptive quantitative approach, supported by secondary data obtained from the Financial Services Authority and the company's official website. The object of research involves Islamic corporate Governance and intellectual capital, corporate financial performance and business sustainability. The population of this research is 14 Islamic commercial banks in Indonesia in 2016 – 2020, with purposive sampling technique, namely companies that publish annual reports including sustainability reports consecutively during the 2016 - 2020. The analytical technique used is Partial Least Square (PLS) with a level of confidence 1.96 which is stated significantly between variable relationships. The results of data processing are in the form of models, journals in reputable international journals, HKI and providing input for policy makers about Islamic banks, for the Islamic banks internal policy and all the investors in making investment decision.